An arachidonic acid generation/export system involved in the regulation of cholesterol transport in mitochondria of steroidogenic cells - Duarte, Alejandra Beatriz (2007)
Recent studies demonstrated the importance of the mitochondrial ATP in the regulation of a novel long-chain fatty acid generation/export system in mitochondria of diabetic rat heart. In steroidogenic systems, mitochondrial ATP and intramitochondrial arachidonic acid (AA) generation are important for steroidogenesis. Here, we report that mitochondrial ATP is necessary for the generation and export of AA, steroid production and steroidogenic acute regulatory protein induction supported by cyclic 3´-5´-adenosine monophosphate in steroidogenic cells. These results demonstrate that ATP depletion affects AA export and provide new evidence of the existence of the fatty acid generation and export system involved in mitochondrial cholesterol transport.